1996
DOI: 10.21273/hortsci.31.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Root Formation by Thiol Compounds

Abstract: Root formation in shoot cuttings of soybean (Glycine max L. `Williams'), mungbean (Phaseolus aureas Mdlbg.), English ivy (Hedera helix L.), and apple (Malus ×domestica Borkh. `Jork 9') was stimulated by dithiothreitol and reduced glutathione in the presence and absence of auxin (IAA) shock. In soybean, in the absence of auxin, root formation was stimulated to about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The inclusion of 10 μM GSH to the medium gave the best results regarding root number and root length of MM106 apple microshoots while 25 μM GSH led to the highest rooting percentage. Similar results were obtained by Auderset et al (1996) in micropropagated apple (Malus x domestica Borkh. 'Jork 9') shoots derived from callus where 25-100 μM GSH augmented the percentage of rooted explants while root number was increased in the 50-75 μM GSH concentration range.…”
Section: Gsh (μM)supporting
confidence: 82%
See 3 more Smart Citations
“…The inclusion of 10 μM GSH to the medium gave the best results regarding root number and root length of MM106 apple microshoots while 25 μM GSH led to the highest rooting percentage. Similar results were obtained by Auderset et al (1996) in micropropagated apple (Malus x domestica Borkh. 'Jork 9') shoots derived from callus where 25-100 μM GSH augmented the percentage of rooted explants while root number was increased in the 50-75 μM GSH concentration range.…”
Section: Gsh (μM)supporting
confidence: 82%
“…Our results are in agreement with those obtained by Nomura et al (1998), who found that 100 μM GSH improved the development of isolated shoot tips of apple. Similarly, in soybean, 100 μM GSH increased shoot length both in the presence and absence of IAA shock alone (Auderset et al 1996). Positive effects of GSH on shoot length were also reported for green onion (Allium cepa L., cv.…”
Section: Gsh (μM)mentioning
confidence: 64%
See 2 more Smart Citations
“…1992; Pawlicki & Welander 1995), polyamines (Rugini et al. 1993) or thiol compounds (Auderset et al. 1996, 1997).…”
Section: Biological Activity Of Urea Derivativesmentioning
confidence: 99%